Cystic lung diseases: radiological aspects. Issue 5 (May 2022) - Valente, T.; Guarino, S.; Lassandro, G.; Picchi, S.G.; Romano, F.; Massimo, C.; Rea, G.; Lieto, R.; Nicola, R.; Lassandro, F.
Abstract : Cystic lung diseases (CLDs) are a heterogeneous group of pathophysiological entities comprising gas-filled lesions with imperceptible walls, which can occur throughout lung parenchyma. CLDs can arise from different mechanisms and may often have an unpredictable progression. As CLDs are infrequent and may be associated to many different processes, they pose a diagnostic challenge to the radiologist and referring physician. CLDs require a comprehensive diagnostic approach. An essential tool in the evaluation of CLDs is high-resolution computed tomography (HRCT). The first step is in distinction from true cysts, from other cysts mimicking entities, as emphysema, honeycombing, pneumatocoele, cavitate nodules, or bronchiectasis. Thereafter the identification of number, distribution, wall size, and other systemic manifestations provides an accurate characterisation of CLD, often avoiding further evaluation with lung biopsy. Features of pulmonary lucencies, classification of CLDs based on pathophysiological mechanisms, and radiological criteria, the less common aetiologies, and a multidisciplinary approach in pulmonary cysts are reported. Finally, a systematic diagnostic algorithm to guide radiologists in the evaluation of CLDs is discussed.